Genetic Diversity of Rice stripe necrosis virus and New Insights into Evolution of the Genus Benyvirus - Bagayoko, Issiaka; Celli, Marcos Giovani; Romay, Gustavo; Poulicard, Nils; Pinel-Galzi, Agnès; Julian, Charlotte; Filloux, Denis; Roumagnac, Philippe; Sérémé, Drissa; Bragard, Claude; Hébrard, Eugénie (MDPI, 2021)
The rice stripe necrosis virus (RSNV) has been reported to infect rice in several countries in Africa and South America, but limited genomic data are currently publicly available. Here, eleven RSNV genomes were entirely sequenced, including the first corpus of RSNV genomes of African isolates. The genetic variability was differently distributed along the two genomic segments. The segment RNA1, within which clusters of polymorphisms were identified, showed a higher nucleotidic variability than did the beet necrotic yellow vein virus (BNYVV) RNA1 segment. The diversity patterns of both viruses were similar in the RNA2 segment, except for an in-frame insertion of 243 nucleotides located in the RSNV tgbp1 gene. Recombination events were detected into RNA1 and RNA2 segments, in particular in the two most divergent RSNV isolates from Colombia and Sierra Leone. In contrast to BNYVV, the RSNV molecular diversity had a geographical structure with two main RSNV lineages distributed in America and in Africa. Our data on the genetic diversity of RSNV revealed unexpected differences with BNYVV suggesting a complex evolutionary history of the genus Benyvirus